A randomised controlled trial comparing the efficacy of single dose prophylactic ceftriaxone versus post-operative ciprofloxacin and metronidazole combination in reducing post-operative wound infection after clean surgeries - Vasu, S.; Sagar, Kshir (International Surgery Journal, 2018)
Background: Surgical site infections were considered to be the major contributor to increased morbidity and mortality in clean surgeries. Many studies prove that single dose prophylaxis is more effective than multiple dosing. No data currently exist about comparative efficacy of single dose prophylactic ceftriaxone with postoperative ciprofloxacin and metronidazole combination in reducing postoperative wound infection after clean surgeries. Hence the present study was done to compare their efficacy in terms rate of incidence of wound infection and side effects. Methods: This prospective study was done on 120 patients who were selected for clean surgeries at Sapthagiri Institute of Medical Science and Research Centre, Bengaluru during the period from April 2015 and March 2016. 60 patients received single dose of ceftriaxone prophylactically and considered as study group and other 60 patients received combination of ciprofloxacin and metronidazole postoperatively for 5-7 days and considered as control group. The efficacy of drugs was estimated in terms of reducing the incidence of wound infection. Results: The wound infection rate was 13.33% in the study group and 28.33% in control. Staphylococcus aureus was the most common organism isolated from wound discharge. However, gram negative organism accounted for majority of infections. There were no major side effects encountered in either of the groups. Conclusions: The study concludes that single dose ceftriaxone can be widely applied in the routine practice in clean surgeries. The single dose ceftriaxone showed many advantages over the control group in terms of Reduced the incidence of postoperative wound infection with no major side effects.